PERAN KEPUASAN KERJA DALAM MEMEDIASI GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL - Dwi Zulkifar Mulyadi; Murdjani Kamaluddin; Sri Wiyati Mahrani (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to examine and analyze: (1) Influence of Leadership Style on job satisfaction (2) influence the style of leadership on organizational commitment (3) the influence of organizational culture on job satisfaction (4) the influence of organizational culture on organizational commitment (5) The effect of job satisfaction on organizational commitment mediated job satisfaction (6) Effect of style leadership on organizational commitment mediated job satisfaction (7) The influence of organizational culture on organizational commitment to employee job satisfaction mediated PT Bosowa Berlian Motor Branch kendari.The population in this study were all employees of PT Bosowa Berlian Motor branch kendari with the number of respondents 43 people. Data analysis tool used is the IMB SPSS 23 and Partial Least Square (PLS).The results showed that: (1) Leadership Style positive and significant impact on job satisfaction (2) leadership style positive and significant effect on organizational commitment (3) organizational culture positive and significant impact on job satisfaction (4) cultural organizations a significant negative effect on organizational commitment (5) job satisfaction positive and significant impact on job satisfaction mediated organizational commitment (6) style of leadership and a significant positive effect on job satisfaction mediated organizational commitment (7) organizational culture positive and significant effect on organizational commitment of employee job satisfaction mediated PT Bosowa Berlian Motor Branch kendari.Keywords: leadership style, organizational culture, job satisfaction, organizational commitment